A case study on asphalt core construction rate for the Zhaobishan embankment dam. (December 2020) - Wang, Weibiao; Hu, Kai; Feng, Shan; Zhao, Ran
Abstract: Traditional construction practices showed that asphalt core construction rate was commonly 2 layers/day (0.4 m/day) before the year 2000. More than 2 layers/day has been concerned as it would be difficult to compact the third layer to reach the required density (void content of maximum 3%) as the sublayers are soft. However, the Zhaobishan embankment dam was located at a very special dam site and high construction rate was required. Based on reviewing successfully high construction rates of asphalt core test section with 0.8 m/day (4 layers/day) and 0.9 m/day (3 layers/day) extensive laboratory tests and 4 trial test sections near the Zhaobishan dam site were carried out to gain asphalt mix parameters and construction techniques before constructing the asphalt core. The 63.6 m high asphalt core for the 71 m high dam was completed in 159 days with intensively quality control during construction. The maximum construction rate was 0.92 m/day (4 layers/day). The dam with asphalt core has performed well since the completion year 2005. The dam case study has documented that asphalt core dam can be constructed in a high rate without compromising core quality. Based on practical experience, field observations, and investigations in recent years, one can now build asphalt core dams faster and more economically than before. The fact that one can significantly reduce the probability of overtopping during construction by increasing the construction rate, may be an important point in many situations.